2020
DOI: 10.21203/rs.3.rs-34588/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can a penalized-likelihood estimation algorithm be used to reduce the injected dose or the acquisition time in 68Ga-DOTATATE PET/CT studies?

Abstract: Background: Both image quality and quantitative accuracy of PET depend on several factors such as uptake time, scanner characteristics and image reconstruction methods. Ordered subset expectation maximization (OSEM) is considered today the gold standard for image reconstruction. Penalized-likelihood estimation (PL) algorithms have been recently developed for PET reconstruction to improve quantitation accuracy while maintaining or even improving image quality. In the present study, we aim to compare the perform… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…For 68 Ga tracer, one preliminary study suggested BPL algorithm with a penalization factor between 350 and 450 could be used in clinical practice for all studied radiopharmaceuticals [15] , while a 68 Gallium-DOTA0-1NaI3-octreotide( 68 Ga-DOTA-TOC) PET study recommended that a factor equal to 400 or higher than 400 could be optimal [16] . However, another 68 Gallium-DOTA0-Tyr3-octreotate ( 68 Ga-DOTA-TATE) PET/CT study concluded that BPL algorithm with the penalization factor within 1100 to 1400 with 1.5 m/b resulted in better image quality than OSEM, while choosing from 1300 to 1600 for 1 m/b also had better image quality [17] . In line with those studies, our study suggested a penalization factor between 0.03 and 0.5 for HYPER Iterative reconstruction that provided higher lesion contrast compare to OSME, while lower image noise was acquired between 0.1 and 0.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For 68 Ga tracer, one preliminary study suggested BPL algorithm with a penalization factor between 350 and 450 could be used in clinical practice for all studied radiopharmaceuticals [15] , while a 68 Gallium-DOTA0-1NaI3-octreotide( 68 Ga-DOTA-TOC) PET study recommended that a factor equal to 400 or higher than 400 could be optimal [16] . However, another 68 Gallium-DOTA0-Tyr3-octreotate ( 68 Ga-DOTA-TATE) PET/CT study concluded that BPL algorithm with the penalization factor within 1100 to 1400 with 1.5 m/b resulted in better image quality than OSEM, while choosing from 1300 to 1600 for 1 m/b also had better image quality [17] . In line with those studies, our study suggested a penalization factor between 0.03 and 0.5 for HYPER Iterative reconstruction that provided higher lesion contrast compare to OSME, while lower image noise was acquired between 0.1 and 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the penalization factor should be xed to maintain the consistency of SUV. In a previous study of 68 Ga-DOAT-TATE PET, the optimal penalization factor was determined from the equivalent noise group which had increased tumor SUV max and improved signal-to-background ratio [17] , while it also depended on lesion detection rate and a high patient throughput in oncologic whole-body 18 F-FDG examinations [14] . Since the radiologists remain the intention to diagnosis as center task, it must be appropriate to consider the raters' preference on the choosing of optimal noise penalization factor.…”
Section: Discussionmentioning
confidence: 99%
“…Die Bayesian penalized Likelihood (BPL)-Bildrekonstruktion ist aktuell als Q.Clear der Firma General Electric (GE) kommerziell verfügbar. Mehrere klinische Studien konnten zeigen, dass die Bildqualität und das Bildrauschen unter Verwendung des BPL-Algorithmus für verschiedene Fluor-18- [49][50][51][52] und Gallium-68-markierte Radiopharmaka [53][54][55] den OSEM-basierten Rekonstruktionsverfahren überlegen sind. Auch konnte bereits mehrfach eine höhere Läsionsdetektionsrate als mit OSEM-basierten Verfahren beobachtet werden, sogar wenn Letztere eine TOF-und/oder PSF-Rekonstruk-FA ZIT Take Home Message Zusammenfassend zeigt die Literatur, dass Verbesserungen der Bildqualität, der zu injizierenden Aktivität und der Läsionsdetektion mit der SiPM-Technologie wahrscheinlich sind, auch wenn es in Patientenstudien schwer ist, den klinischen Mehrwert gegenüber PMT-basierten Scannern einwandfrei nachzuweisen.…”
Section: Bildqualität Und Läsionsdetektionunclassified